2010
DOI: 10.1096/fj.10-163790
|View full text |Cite
|
Sign up to set email alerts
|

Reactive glial cells: increased stiffness correlates with increased intermediate filament expression

Abstract: Increased stiffness of reactive glial cells may impede neurite growth and contribute to the poor regenerative capabilities of the mammalian central nervous system. We induced reactive gliosis in rodent retina by ischemia-reperfusion and assessed intermediate filament (IF) expression and the viscoelastic properties of dissociated single glial cells in wild-type mice, mice lacking glial fibrillary acidic protein and vimentin (GFAP(-/-)Vim(-/-)) in which glial cells are consequently devoid of IFs, and normal Long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(118 citation statements)
references
References 32 publications
3
113
0
2
Order By: Relevance
“…Furthermore, in reeler mice, which lack the extracellular matrix glycoprotein reelin, an increase in the number of glial fibrillary acidic protein (GFAP)-positive astrocytes is accompanied by a decrease in the number of newly generated neurons (Zhao et al, 2007), and enhanced GFAP expression in retinal glial cells leads to their stiffening (Lu et al, 2011). The enhanced GFAP expression in the mouse mutants could thus lead to an increase in tissue stiffness that causes, or at least contributes to, the observed decrease in neurogenesis.…”
Section: Neurogenesismentioning
confidence: 99%
“…Furthermore, in reeler mice, which lack the extracellular matrix glycoprotein reelin, an increase in the number of glial fibrillary acidic protein (GFAP)-positive astrocytes is accompanied by a decrease in the number of newly generated neurons (Zhao et al, 2007), and enhanced GFAP expression in retinal glial cells leads to their stiffening (Lu et al, 2011). The enhanced GFAP expression in the mouse mutants could thus lead to an increase in tissue stiffness that causes, or at least contributes to, the observed decrease in neurogenesis.…”
Section: Neurogenesismentioning
confidence: 99%
“…In the retina, the biochemical and biomechanical homeostasis is maintained by Müller cells, which can alter their physical properties through up-or downregulation of intermediary filaments (such as GFAP and vimentin) [11,12,22,23]. This allows Müller cells to control the tissue-wide as well as the cellular biomechanical environment [11,12,22,23].…”
Section: Müller Cell Activationmentioning
confidence: 99%
“…This allows Müller cells to control the tissue-wide as well as the cellular biomechanical environment [11,12,22,23]. In this setting, it is interesting to note that the stiff, intermediary filament-rich Müller cell endfeet contain mechanosensory cation channels, such as TRPV4, which are known to respond to changes in cell membrane stretch through Ca2+ influx [11,12,[22][23][24]. Influx of Ca2+ is a known trigger of intermediary filament upregulation in Müller cells [12,25,26].…”
Section: Müller Cell Activationmentioning
confidence: 99%
“…At the individual astrocyte level, atomic force microscopy analysis showed that reactive changes in the cytoskeleton, including increased GFAP content, are associated with increased stiffness (that is, increased elasticity) of individual cells. 18 Although the testing method used here offers a very high degree of precision, the numeric values cannot be considered as accurate material property constants. The measured values are intimately related to the details of the testing method.…”
Section: Fig 3 Uppermentioning
confidence: 99%